Mesenchymal stromal cells storage at ambient temperature - Hubenia, O.; Trufanova, N.; Kot, Yu. (My University, 2022)
Mesenchymal stromal cells (MSCs) possess high proliferative potential, the ability to multilinear differentiation, low immunogenicity and immunomodulatory properties. MSCs are increasingly used in various fields of biology, tissue engineering, etc. Short-term storage at ambient temperatures may both solve problem of cell injury associated with cryopreservation and simplify transportation between clinical centers.
Keywords: Mesenchymal stromal cells, alginate, viability, cell cycle, reactive oxygen species